Vehicle recognition system using RFID technology for parking management system - Ng, Kay Li; Chiong, Raymond; Reine, Regina (2018)
© Published under licence by IOP Publishing Ltd. Technology is growing each day by leaps and bounds. The change in technology has done wonders to increase productivity in everyday life. However, drivers searching for parking contributed to traffic congestion especially in urban and suburban cities, while consuming their time and energy. Besides, traffic congestion in parking area is always an issue which contribute to traffic on the main road. The current approach to overcome this includes the implementation of parking ticket system, especially in busy area. The hour rate for busy area is elevated to promote liquidation of vehicles. However, this system requires patrol warden to manually inspect each vehicle for the parking ticket. The feasibility of the system decreases when the parking area is larger. RFID parking management system aims to bring automation into parking system. The use of passive UHF RFID which can read multiple tags from long distance can replace patrol warden and thus increase the effectiveness of the Vehicle Parking Management System (VPMS). Furthermore, the power consumption of RFID system is analyzed. A new method has been introduced to reduce the power consumption of RFID system which operates 24/7. Experimental results demonstrate the effectiveness of the proposed method in reducing the power consumption of the RFID system.